Implementing BiSM and CCL algorithm for managing audio storage - Hamzah, Hammuzamer Irwan; Low, Tan Jung (2012)
Audio files are stored in many devices such as computers, laptops, smartphones, iPods and etc.These devices also store other multimedia files.Hence, there are limited spaces for the devices with small hard disk. Therefore, this paper analyzed the issues and proposed a solution to manage the audio storage.The elements from biological inspired components were studied and identified to seek for the requirements of Bio-Inspired Storing Model (BiSM).Then a structural architecture of BiSM was designed in addition the Cognitive and Constructive Learning (CCL) algorithm was proposed.Finally, BiSM and CCL algorithm were evaluated with exemplar application settings and the results were presented in a case study of MP3 music collections.